Jurnal Teknologi Metaverse Sebagai Peluang Untuk Meningkatkan Pariwisata di Danau Toba - Rizki Nurul Nugraha; Ardissa Dwi Eranti (Peneliti.net, 2023)
Metaverse technology can help all aspects of life in the economic, educational and business fields. however, limited information and literacy can have a negative impact, so socialization about the metaverse is needed. This study analyzes to see the effectiveness of economic opportunities in (Lake Toba tourism: example) through metaverse tourism. This study uses a descriptive qualitative method by utilizing secondary data and interviews to strengthen references and confirm the data found during the study. The virtual world in tourism has opened up new possibilities for innovation in enjoying travel. Adapting to technology that is environmentally friendly and has a positive impact on preserving nature without having to be afraid of negative issues that will reduce the interest of tourists to come to visit to enjoy natural phenomena and travel in (Lake Toba: example). Indonesia must be ready to face this technological metaverse because in the future the world will change.